Monetary policy and sectoral stock market in Malaysia - Lee, Ka Shing; Karim, Zulkefly Abdul (Universitas Islam Indonesia, 2025)
Purpose ― This paper aims to examine the extent to which monetary policy shocks (domestic and international) will affect the movement of the sectoral stock index in Malaysia.Methods ― The monetary policy shocks are identified using a structural vector autoregressive (SVAR) model to examine the propagation of both monetary policy shocks (domestic and international) on sectoral stock prices.Findings ― The main results show that foreign monetary shocks significantly affect four sectoral stock indices: industrial and services, plantation, telecommunications, and utilities. In contrast, domestic monetary shocks impact three sectoral indices: industrial and services, technology, and utilities. However, domestic monetary policy shocks have a more dominant effect on the sectoral stock market in terms of magnitude.Implication ― The analysis results provide policymakers, particularly Bank Negara Malaysia (BNM), with valuable insights into which sectors are most sensitive to monetary policy fluctuations. Additionally, the results are beneficial for investors, as the analysis can help them manage their assets more effectively by identifying which sectoral stock indices are most affected by both domestic and international monetary policy shocks, and by guiding them to make more accurate investment decisions.Originality — First, it focuses specifically on sectoral indices, examining all 13 in Malaysia through the lens of theory, with particular emphasis on impulse-response analysis, which explores the cumulative effects of both domestic and foreign monetary policy shocks on these indices. Secondly, the study employs a lagged analysis using the SVAR model, providing a theoretical framework for comparison with other relevant studies.